Need Analysis on Development of Teaching Writing Materials ‘Genre’ Based on Gayo Local Culture - Khoiriyah Shofiyah Tanjung (Jurnal Educative: Journal of Educational Studies, 2019)
The research aims to analyze the needs of development teaching writing material ‘genre’ based on students’ local culture in Central Aceh. Mix methodologies are conducted in collecting the data, interviewing the teacher and giving the questionnaires to the students. The participants of this research are two English teachers and thirty students of tenth grade from two different Islamic High Schools in Central Aceh. The samples are taken by conducting purposive sampling. The result of the study showed three things; first, writing is the most difficult skill for students to be mastered, second, teaching material based on local culture has not been available yet, the last, teaching writing material ‘genre’ based on local culture is needed in order to improve students’ writing ability.